Fate, transport, and risk assessment of widely prescribed pharmaceuticals in terrestrial and aquatic systems: A review - Jamal F. Shaheen; Banu Sizirici; Ibrahim Yildiz (Emerging Contaminants, 2022)
Rapid development of pharmaceuticals outpaces the efforts to regulate and monitor their trace concentrations in the environment. This emerging issue can only be solved through field studies, solid fate and transport models, and adequate risk assessment of the concerned contaminants. This approach requires the availability of toxicological information about the contaminants along with an understanding of their full potential in different media of the environment. This review paper focuses on commonly used seven pharmaceutical families across the globe: antacids, antibiotics, antidepressants, antiepileptics, beta blockers, lipid lowering drugs, and nonsteroidal anti-inflammatory drugs. Within each family, pharmaceuticals which are widely prescribed, studied, and frequently detected in environment were selected. The concentration levels in the environment, updated physicochemical properties, main natural removal mechanism, and ecological risk assessment towards the receptors of those pharmaceuticals in aquatic and terrestrial systems were analyzed. The following results were observed in the literature: 1) removal of the pharmaceuticals from wastewater treatment plants is reduced when the dissolved organic matter present; 2) many studies have cited older physicochemical properties of the concerned pharmaceuticals assuming relative conditions in their studies which can affect the accuracy of a model; 3) the number of studies are very limited for fate and transport in the soil; and 4) there is lack of cumulative risk assessment of mixed pharmaceutical substances. Therefore, this review will provide modeler with updated physiochemical properties; it will guide researchers to focus on removal of those contaminants at different lifecycle stages; and it will provide guidance to policy makers to develop effective policies and regulations.